That's thee, uuh blicket! How does disfluency affect children's word learning?. Issue 1 (February 2020) - White, Katherine S.; Nilsen, Elizabeth S.; Deglint, Taylor; Silva, Janel
Disfluencies, such as 'um' or 'uh', can cause adults to attribute uncertainty to speakers, but may also facilitate speech processing. To understand how these different functions affect children's learning, we asked whether (dis)fluency affects children's decision to select information from speakers (an explicit behavior) and their learning of specific words (an implicit behavior). In Experiment 1a, 31 3- to 4-year-olds heard two puppets provide fluent or disfluent descriptions of familiar objects. Each puppet then labeled a different novel object with the same novel word (again, fluently or disfluently). Children more frequently endorsed the object referred to by the fluent speaker. We replicated this finding with a separate group of 4-year-olds in Experiment 1b ( N = 31) and a modified design. In Experiment 2, 62 3- to 4-year-olds were trained on new words, produced following a disfluency or not, and were subsequently tested on their recognition of the words. Children were equally accurate for the two types of words. These results suggest that while children may prefer information from fluent speakers, they learn words equally well regardless of fluency, at least in some contexts.